Contrast-enhanced ultrasound and elastography predict histopathology and recovery in acute kidney injury - Xiangyu Wang; Jiajia Liu; Luzeng Chen; Tao Su (Renal Failure)
Purpose Acute kidney injury (AKI) progression involves complex microcirculatory and structural changes poorly captured by conventional metrics. This study investigates contrast-enhanced ultrasound (CEUS) and shear wave elastography (SWE) to evaluate hemodynamic redistribution and fibrosis in AKI patients.Methods Prospective cohort study of 16 biopsy-confirmed tubulointerstitial (TI) nephritis patients and matched controls. We aim to explore the potential correlation of CEUS–SWE derived parameters (peak intensity (PI), rise time (RT), time to peak (TTP), and shear wave velocity (SWV)) with renal histopathology and 3-month outcomes (renal recovery: estimated glomerular filtration rate (eGFR) ≥45 mL/min/1.73 m2).Results CEUS revealed stage-specific perfusion patterns: milder AKI (eGFR >25 mL/min/1.73 m2) showed medullary hyperemia (cortical-to-medullary PI ratio: 0.80 ± 0.24 vs. 1.12 ± 0.18 in controls; p < .05), a potential compensatory response to medullary hypoxia. Cortical-to-medullary ratios of PI, RT, and TTP significantly correlated with chronic TI injury (r = 0.501/−0.576/−0.547), reflecting capillary rarefaction’s role in disease severity and fibrosis. Patients with severe renal dysfunction (eGFR <25 mL/min/1.73 m2) exhibited elevated renal artery resistive indices. In stage 3 AKI, PI ratio demonstrated positive correlation with glomerulosclerosis (r = 0.690, p = .03), cortical RT/TTP correlated inversely with chronic TI injury (r = −0.807/−0.821, p = .005/.004), reflecting cortical hypoperfusion and impaired compensatory perfusion redistribution during AKI. Prognostically, patients with lower PI ratio (indicating preserved medullary hyperemia) experienced better renal recovery (64.3% achieving eGFR ≥45 mL/min/1.73 m2; p = .02). SWE-derived SWV declined with AKI severity (p < .05) but lacked fibrosis specificity due to edema/necrosis confounders.Conclusions CEUS-derived PI ratios quantify microcirculatory dysfunction in AKI, correlating with chronic TI injury and predicting recovery.